(untitled) (Proceedings of the International Conference on Future of Education, 2022)
Instructional materials assume a central role to successful teaching and learning at the time of a pandemic. This study excerpt focused on the extent, applicability, and student satisfaction on the use of instructional materials utilized by research teachers in senior high schools in the Philippines, along with other study variables. Quantitative study design using the survey technique was employed and had generated 1, 250 valid responses from college students all over the country. Findings showed that the majority of the participants were female, who graduated from the academic track in public senior high schools, particularly from the General Academic Strand. Findings revealed the use of instructional materials by their previous senior high school teachers to teach them research, and they are generally ‘Satisfied’. Further, they claimed that such instructional materials in research could be applicable for instruction during the pandemic but, ironically, they also recommend that more student-friendly materials suitable for distance learning still be written. Further, statistical analysis evinced that ‘Strand Type’ but not Gender Identity, School Type, and School Track, appeared to be a moderator variable that influences the level of their satisfaction on the use of IMs and the choice to recommend a more student-friendly instructional material. With these findings, the researchers proposed a curriculum for a possible pattern of non-face-to-face research teaching for beginners and recommended periodic evaluation of the same once implemented in the field.